Hand carried echocardiography screening for LV systolic dysfunction in a pulmonary function laboratory - Kirkpatrick, James N.; Ghani, Syed Nasir; Spencer, Kirk T. (European journal of echocardiography, 2008)
Aims Dyspnea is a common indication for pulmonary evaluation but also a common symptom in heart failure. Identification of dyspneic patients with significant LV systolic dysfunction is critical because of high morbidity of untreated heart failure. We sought to determine whether screening patients referred for pulmonary function testing (PFT) using a hand carried ultrasound (HCU) device could identify LV systolic dysfunction. Methods Forty-nine subjects were recruited from a pulmonary function lab to undergo a brief echocardiographic examination by an internist using a HCU device. All subjects also received an examination with a full-featured echocardiogram machine as a gold standard. Results All subjects with normal PFT had normal LV systolic function. Among subjects with abnormal PFT, 6 (15%) had LV systolic dysfunction and the remainder had normal LV systolic function. No subjects with LV systolic dysfunction by full-featured echocardiograms were missed by the HCU (sensitivity 100%, specificity 95%, negative predictive value 100%, positive predictive value 75%). Conclusions LV systolic dysfunction is prevalent among patients with pulmonary disease and can be accurately screened for by a physician using a hand carried ultrasound device with subsequent confirmation with complete echocardiography.